DETERMINAN PAJAK BADAN SEBELUM DAN SESUDAH KONDISI EKONOMI TERDAMPAK COVID-19 PADA PERUSAHAAN LQ-45 YANG TERCATAT DI BURSA EFEK INDONESIA - Sari Zawitri; Elsa Sari Yuliana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2021)
The purpose of this research is to determine the Impact of Changes and Effects of Income and Expenses on Corporate Taxpayers affected by Covid 19 listed on the Indonesia Stock Exchange. This research is a quantitative descriptive research using causal comparative research. The data collection technique done by using indirect observation and literature study. Data analysis done with multiple linear regression and the partial and simultaneous hypothesis testing. The research results show that by the year 2020 almost 50% of listed companies LQ-45 experienced a decline in revenues, expenses, and taxes impact of Covid-19. In the fiscal year 2019, income had a positive and significant effect on 0.000 with a tcount of 8.901 and expenses had a negative and significant effect on 0.015 with a tcount of -2.524. Meanwhile, for the fiscal year 2020, the independent variables of income (X1) and expenses (X2) simultaneously have a positive and significant effect of 0.000 on taxes (Y) with an Fcount of 159,292. The research output is for knowing the impact of Covid 19 on revenues, expenses, and taxes as a consequence of Government policies.